#TITLE_ALTERNATIVE# - Bagus Seno Wulung (NIM 234 06 051), Raden
Abstract: Leather industry is a potential industry in Indonesia since it can absorb large number of workers, has high value product and utilizes renewable resources. However, in the last 5 years, it exhibits competitiveness degradation and value-added decline. This research is intended to identify critical factors affecting the value-added and competitiveness of Indonesias leather industry. A logit model is used in this research to identify the critical factors influencing the value-added and competitiveness of Indonesias leather industry. The logit model is used since some dependent variables have binary values (binary logit), multinomial values (multinomial logit) and scale values (ordinal logit). The logit regression assumes that the relation between dependent variable and independent variables has an S curve. When the values of independent variables are very low, the probability of dependent variable is close to zero. On the other hand, if the values of independent variables are very high, then the probability of dependent variable is close to one. The results of this research indicate that most of Indonesias leather industries are small- and medium-scale enterprises. The results show that supports from local universities and research centers for developing the technology required by the leather industry is yet limited and differ among the companies. The companies which have highly qualified human resources and R&D unit tend to receive more sophisticated technology compared to their counterparts with lack of qualified workers and R&D facility. Besides, innovations may increase the value-added created by the companies with human resource quality, quality management system, and R&D unit as the most influencing factors. This research also indicates that technology transfers takes place at the upper stream of the industry, from the buying companies to their suppliers. Another result of the research is that Indonesias leather industry has high dependence on imported technology, in particular in form of equipment and chemical substances.